Efficient decentralized multi-authority attribute based encryption for mobile cloud data storage. (1st March 2019) - Arthur Sandor, Voundi Koe; Lin, Yaping; Li, Xiehua; Lin, Feng; Zhang, Shiwen
Abstract: Mobile cloud data storage allows mobile users to outsource personal and corporate data to the cloud for flexibility and money savings. However, data outsourcing introduces high confidentiality and privacy risks. To solve the above issues in mobile cloud data storage, attribute-based encryption has been proposed thanks to the flexibility in encryption policy and the fine grained access control. Existing multi-authority attribute-based encryption schemes however still require a trusted central authority to publish system parameters and to generate user secret keys. They give to the trusted central authority enough privileges to access the plaintext information meant for the user, a problem referred to as key escrow issue. They moreover require high computational and communicational overhead on the different operating entities. We propose in this paper an efficient decentralized multi-authority attribute-based scheme for mobile cloud data storage. Our scheme solves the key escrow problem by removing the central authority, without making use of any global user identity. We demonstrate that our scheme is flexible and exhibits less communication and computation overhead on the data user side, both in an online and offline fashion, as well as prove its security under the decisional bilinear diffie-hellman assumption.